2018
DOI: 10.1111/tid.13002
|View full text |Cite
|
Sign up to set email alerts
|

Successful heart‐kidney transplantation from a Hepatitis C viremic donor to negative recipient: One year of follow‐up

Abstract: Every year the number of patients waiting for a heart transplant increases faster than the number of available donor organs. Some potential donor organs are from donors with active communicable diseases, including hepatitis C virus (HCV), potentially making donation prohibitive. The advent of direct-acting antiviral agents for HCV has drastically changed the treatment of HCV. Recently, these agents have been used to treat HCV in organ donor recipients who acquired the disease from the donor organ. We report a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Selected epidemiological and descriptive characteristics of the transplant recipients are described in Table 3. Four patients (8%) underwent a multiorgan transplantation, 3 of these patients (6%) received a combined heart-kidney transplant 38,40,45 and 1 patient (2%) received a heart-liver transplant. 34 The majority of patients (n = 16, 47%) received basiliximab as induction.…”
Section: Resultsmentioning
confidence: 99%
“…Selected epidemiological and descriptive characteristics of the transplant recipients are described in Table 3. Four patients (8%) underwent a multiorgan transplantation, 3 of these patients (6%) received a combined heart-kidney transplant 38,40,45 and 1 patient (2%) received a heart-liver transplant. 34 The majority of patients (n = 16, 47%) received basiliximab as induction.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, there have been several reports on positive outcomes in patients receiving combined organ transplants (eg, heart/kidney or lung/liver) from HCV-infected donors. 16,18,21 ACCEPTING HCV-INFECTED DONOR ORGANS: PROCEED WITH CAUTION There are several important considerations when using HCV-infected donor organs, as illustrated in Figure 2.…”
Section: Utilization Of Hcv-infected Organs In Transplant Settingsmentioning
confidence: 99%
“…Despite down-trending cost with market competition, DAA therapy can range from $26,400 to $94,500 for an 8-to 12-week course. 21,23 Woolley and colleagues 13 showed that recipients treated within hours of transplantation achieve SVR within 2 weeks, potentially allowing a shorter course of DAA therapy. There have been reported cases of HCV-related complications such as acute glomerulonephritis and cholestatic hepatitis related to delayed access to DAA therapy.…”
Section: Insurance Coveragementioning
confidence: 99%
See 1 more Smart Citation
“…Although 2 recipients became seropositive for HCV antibody and one recipient had a HCV antibody that was equivocal, there was no evidence of viral transmission in all 14 recipients [53]. Wetterston et al described a case of a HCV negative patient with a left ventricular assist device (LVAD) driveline infection and ESRD on hemodialysis who underwent heart-kidney transplant with organs from a HCV-viremic (NAT positive) donor [55]. The recipient developed HCV viremia (genotype 1a) the day after transplant and was started on a 12week course of elbasvir-grazoprevir at the time of discharge and achieved SVR.…”
Section: Heartmentioning
confidence: 99%